Jurisprudential analysis on the protection of farm workers in Colombia - Velasco-Piamba, Juan David (DIXI, 2023)
The purpose of this article is to analyze the rulings issued by the Constitutional Court, in order to extract the rights and guarantees of peasant and rural workers in Colombia. For this purpose, a methodology with a qualitative approach will be used on the pronouncements of the Constitutional Court that the author considers essential to understand what has been granted to this group of rural workers, who have suffered due to the violence of illegal groups and the neglect of different governments; consequently, his population universe will be the documentary. As for the results, we found that some constitutional rights were taken into account during the constitutional drafting and subsequent jurisprudential evolution as subjects of special protection, but that at the level of International Law there is a lack of attention by the State. In conclusion, at the constitutional and jurisprudential level, this social group has a series of rights that, although they are sufficient at the national level, have not been fully protected by the institutions.
Keywords: constitutional jurisprudence; peasant worker; violence in Colombia; subject of special protection; right of access to land